The economics of renewable energy support - Abrell, Jan; Rausch, Sebastian; Streitberger, Clemens (Journal of public economics, 2019)
This paper uses theoretical and numerical economic equilibrium models to examine optimal renewable energy (RE) support policies for wind and solar resources in the presence of a carbon externality associated with the use of fossil fuels. We emphasize three main issues for policy design: the heterogeneity of intermittent natural resources, budget-neutral financing rules, and incentives for carbon mitigation. We find that differentiated subsidies for wind and solar, while being optimal, only yield negligible efficiency gains. Policies with smart financing of RE subsidies which either relax budget neutrality or use polluter-pays financing in the context of budget-neutral schemes can, however, approximate socially optimal outcomes. Our analysis suggests that optimally designed RE support policies do not necessarily have to be viewed as a costly second-best option when carbon pricing is unavailable.
Gesehen am 28.03.2023